Prevalence and associated factors of insomnia symptoms after ending China’s dynamic zero-COVID policy: a cross-sectional survey of frontline nursing staff in Chinese hospitals - Zhang, Ming; Chi, Chenru; Liu, Qingwei; Zhou, Ningying; Zhou, Zhiqing; Tao, Xiubin; Xuan, Bin; Liu, Huan (Frontiers in Public Health, 2024)
After the Chinese government announced the end of the dynamic zero-COVID policy on January 8, 2023, the COVID-19 pandemic peaked. Frontline nursing staff are at high risk of infection transmission due to their frequent contact with COVID-19 patients. In addition, due to the ending of China's dynamic zero-COVID policy, frontline nursing staff have grappled with increased workload, fatigue, and more. This study aimed to explore the prevalence of insomnia symptoms in frontline nursing staff and its influencing factors following the end of the policy.Between January to February 2023, this study was conducted by the Wenjuanxing platform to survey frontline nursing staff in a hospital in Wuhu City, Anhui Province.All the nursing staff included in this study had a COVID-19 infection. The questionnaires included the Athens Insomnia Scale (AIS), PC-PTSD-5 Chinese Version Scale, the Fear of COVID-19 Scale, The 2-item Connor-Davidson Resilience Scale (CD-RISC-2) Scale, and the burden of COVID-19 Scale. Binary logistic regression methods were used to identify variables associated with insomnia symptoms.Among the 694 frontline nursing staff, 74.5% (517/694) exhibited insomnia symptoms. Fear of COVID-19 (P<0.001), the burden of COVID-19(P<0.05), PTSD(P<0.001), and higher technical titles(P<0.008) were highly correlated with insomnia symptoms in frontline nursing staff. Psychological resilience (P<0.001) was a protective factor for insomnia symptoms among frontline nursing staff.After ending China's dynamic zero-COVID policy, the prevalence of insomnia symptoms among frontline nursing staff is generally higher. This study highlights the association between insomnia symptoms and PTSD, fear of COVID-19, COVID-19 burden, and resilience. Psychological assistance is needed for frontline nursing staff to prevent insomnia symptoms and protect the mental health of frontline nursing staff after the end of China's dynamic zero-COVID policy.